PERAN MODEL TEAMS GAMES TOURNAMENT (TGT) DALAM MEMBANGUN KOLABORASI DAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Widi Arta, Komang Mangku; Ni Nyoman Kurnia Wati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning in elementary schools is not only oriented toward academic achievement but also toward the development of students’ social skills and learning motivation. One cooperative learning model that integrates academic and social aspects is the Teams Games Tournament (TGT) model. This study aims to examine the role of the TGT model in fostering collaboration and learning motivation among elementary school students. The research employed a library research method by analyzing ten relevant scientific articles published between 2021 and 2025. Data sources were obtained from nationally accredited journals indexed in SINTA and Google Scholar and analyzed using descriptive content analysis techniques. The results of the review indicate that the implementation of the TGT model consistently enhances students’ collaborative skills, including teamwork, group responsibility, communication, and mutual respect. In addition, TGT plays a significant role in increasing both intrinsic and extrinsic learning motivation through the integration of game-based activities, healthy competition, and group rewards. Collaboration and learning motivation within TGT-based learning interact and form a positive cycle that supports active student engagement in the learning process. Therefore, the Teams Games Tournament model is considered relevant and effective for elementary school learning as an effort to create active, enjoyable, and meaningful learning that supports the development of students’ academic and social potential.